Professional learning community: A pilot study - Abu Hassan, Mohd Aizat; Musa, Kamarudin; Mohd Yusof, Nur Raihan (Management Research Journal, 2019)
This pilot study was conducted to test the reliability of the Professional Learning Community questionnaire which involved eight dimensions, namely norms and joint vision, commitment and support of school principal, structural support, mutual understanding and beliefs, collaborative learning, reflective dialogue, collective inquiry and external support. The design of this study is a quantitative study using SPSS to test the reliability of the instrument by using Cronbach Alpha. A total of 100 respondents were involved with this study to answer the questionnaire. This questionnaire has 63 items and uses the Likert scale. Each item has six answer options namely the scale of the Likert scale from scale one which shows the respondents strongly disagree with the item's statement to scale six which shows the respondents strongly agree with the item's statement as stated in the questionnaire. Overall Alpha Cronbach Value for Professional Learning Community instrument with eight dimensions is between 0.82 to 0.93.